Measuring service quality of light rail transit - Chan, Keong Meng (2000)
The public transportation industry is modernizing with new products being introduced to improve service provision to the public. This is also true for Malaysia whereby the LRT has been introduced. Consumer awareness in evaluating the quality of service in transport has also improved. This research paper studies the LRT customers' perceived service quality of what the LRT operator provides. This paper attempts to discover what the LRT commuters think of the service quality provided by the LRT operator through the 5 SERVQUAL dimensions - Tangibles, Reliability, Assurance, Empathy, and Responsiveness. Data was collected through direct face-to-face interviews with LRT commuters and the processed using the SPSS package. The research findings show that the LRT commuters at the Bukit Jalil and Chempaka LRT stations and the shopping centers at Midpoint and Endah Parade knows of the LRT and have taken it before. The survey results showed the commuters perception scores were lower than the expectation scores. Thus in the eyes of the passengers, the actual LRT service falls below their expectations. There are a lot of improvements which the LRT operator will need to do to bring the service up to commuters expectations of Service Quality to ensure an increase in ridership. This clearly shows that Malaysian commuting public have higher expectations now as the modern LRT service also falls below their expectations when a few years back we only have old rickety buses on the road.